Effect of Rate and Time of Nitrogen Application on Nutrient Content and Uptake in Summer Maize (Zea mays L.) and Soil Nutrient Status After Harvest - Y. B, Madagoudra,; Chaithanya, Jakkannagari; Terin, Prakash; R, Lokesh, (International Journal of Economic Plants, 2021)
A field experiment was conducted at College Farm, N. M. College of Agriculture, Navsari Agricultural University, Navsari to study the effect of rate and time of nitrogen application on quality of summer maize. The treatments of the study included three rates (60, 90 and 120 kg N ha-1) of nitrogen and three timings (two equal splits at sowing and 30 DAS, three equal splits at sowing, 30 and 45 DAS and four equal splits at sowing, 30, 45 and 60 DAS). Nitrogen, Phosphorus and Potassium content in grain and straw were determined by Modified Kjeldahl’s method, Vanadomolybdo phosphoric acid colorimetric method and Flame photometric method, respectively. Nutrient content was multiplied by yield to calculate nutrient uptake (kg ha-1). Available N, P2O5 and K2O were determined by Alkaline permanganate method, Olsen’s method and Flame photometric method, respectively. The rate and time of nitrogen had significant effect on nitrogen content in grain and straw. Phosphorus and Potassium content were non-significant. Nitrogen application at 120 kg ha-1 resulted in significantly higher nitrogen content and uptake. Nitrogen application in four equal splits at sowing, 30, 45 and 60 DAS resulted in higher N content and uptake. Similar results were observed in case of available N in soil after harvest. The available soil P2O5 and K2O remained non-significant.